С.Я. БОРОВИЙ: ДОСЛІДНИК ІСТОРІЇ ЄВРЕЇВ В УКРАЇНІ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the heritage of a historian S. Borovoy (1903-1980). It represents the analysis of the works of the scientist on Jewish culture and history. A great attention is paid to analysis of history of Jews in Ukraine in XVI-XVIII century.